Roles of Oxygen Vacancies in NiMoO4: A First-Principles Study - Wen, Yuanbin; Wang, Pengcheng; Ding, Xinying; Feng, Xiaobo; Qing, Chen (Frontiers in Energy Research, 2021)
Oxygen vacancy have been suggested to play a role in the electrochemical ability of NiMoO4. The band structure and density of state of NiMoO4 bulks with different concentrations of oxygen vacancy were investigated by the first-principles calculation. Original NiMoO4 shows semi-conductive properties with a direct band gap of 0.136 eV. When one to three oxygen vacancies were introduced in the NiMoO4 supercell, the band structure of NiMoO4 transforms to metallic properties and oxygen vacancies formation energy increases with the increase number of oxygen vacancies. The oxygen vacancies in NiMoO4 leading to increased electron localization of Ni 3d and Mo 3d state nearby the fermi level, which resulting in higher concentration of carriers in NiMoO4 and thus increase its electrical conductivity. The results demonstrate that introducing oxygen vacancies can improve the conductive property of NiMoO4.